Coronary Artery Disease Awareness: Levels of Socioeconomic Status and Dietary Restriction - Prasad, Snehita; Mishra, Mritunjay Kumar; Yadav, Tapeshwar (Nepal Journal of Health Sciences, 2021)
Introduction: India has undergone a remarkable demographic transition over the period time. Socioeconomic status indicators including education, income, and occupation are associated with coronary heart disease risk factors, morbidity, and mortality. Objective: To assess the socioeconomic status and diet restriction in patients with coronary artery diseases. Methods: The present study was a type of observational study conducted on total 200 subjects in Dhiraj Hospital, Sumandeep Vidyapeeth from August-2019 to July-2020 after ethical approval. Out of which 100 were coronary artery diseases and 100 were healthy controls. Patients with other than coronary artery diseases were excluded from the study, data were collected with the help of a pre-validated questionnaire and analyzed by SPSS-16 software. Results: Eighty-nine subjects with coronary artery diseases and seventy-five healthy controls were physically inactive. Eighty-five subjects with coronary artery diseases do not have any diet restriction, however, fifty-nine subjects had exposure to only primary education. Conclusion: Majority of the subjects were from a rural area, there were high illiteracy levels so there was low awareness. Patients could come to know the importance of physical activities and how to maintain a normal weight by following a dietary regimen to minimize the risks of disease.